Studies on Transferrin-DNA conjugates for gene delivery to cells and animal tissues - Robinson, P. J.(Philippus Johannes),1932- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Med. Sci.) -- Universiteit van Stellenbosch, 1996.